IDENTIFIKASI DAN KARAKTERISASI ISOLAT BAKTERI ASAM LAKTAT POTENSI PROBIOTIK PENSINTESIS CONJUGATED LINOLEIC ACID (CLA) - , NOSA SEPTIANA ANINDITA; , Widodo, S.P., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
aims The of this study was to identify and characterize potential probiotics with the ability to synthesize bioactive compounds CLA. Five isolates of LAB isolated from faeces of infants who consumed breast milk as the only source of diet were grown on L-cysteine-supplemented MRS Agar and incubated on 37Â°C for 48 hours. Colonies grew on this media were then phenotypically identified based on morphological and biochemichal, followed by genotypic identification. Phenotypic identifications based on Gram staining, catalase, motility, spore forming, CO2 production, and the ability to grow on different temperatures, pH and concentration of salt. Genotypic identification relied on the amplification of sequence of 16S rRNA gene. The potential application of selected isolates for probiotics was evaluated based on the ability to grow on media with low pH and bile salts, the ability to inhibit the growth of pathogen, in vitro adherence ability on pig gastric mucin and to utilize inulin as the only carbon source. Based on the identification of cellular, biochemical and 16S rRNA gene analysis, isolates AP and AG were classified as Lactobacillus casei (99%), whereas isolates AA, BE and BK were classified as Pediococcus acidilactici (99%). In vitro evaluation of five isolates showed potential candidate as probiotic through several test parameters. Evaluation on the ability to use prebiotic inulin as carbon source showed that Lactobacillus casei (strain AP and AG) and Pediococcus acidilactici strains BE had the ability to degrade inulin as a prebiotic. Selection of candidate probiotic isolates to synthesize Conjugated Linoleic Acid (CLA) from free linoleic acid showed that Lactobacillus casei strain AP was able to convert more than 60% of free linoleic acid to CLA in the media. The data obtained indicated that the selected isolate Lactobacillus casei strain AP is potential candidate for probiotic application and produce CLA.